2008
DOI: 10.1002/chin.200828114
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Efficient Preparation of the Isoindoline Framework via a Six Component, Tandem Double A3‐Coupling and [2 + 2 + 2] Cycloaddition Reaction.

Abstract: Tetrasubstituted isoindoles are prepared in a single synthetic operation from a primary aniline, three phenylacetylene units, and two formaldehyde units via three consecutive reactions, two aldehyde-amine-alkyne couplings catalyzed by CuBr, and a final [2 + 2 + 2] cycloaddition catalyzed by the Wilkinson's catalyst. -(BONFIELD, E. R.; LI*, C.-J.; Adv.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Direct Alkynylation of Glycine Amides via CDC Reaction Catalytic Nucleophilic Additions of Terminal Alkynes Li ous formaldehyde units, and a primary amine in a single synthetic operation by using a combined copper/rhodium catalyst (eq 20). 76 …”
Section: Addition Of Terminal Alkyne To Imine Tosylimine Iminium Iomentioning
confidence: 97%
“…Direct Alkynylation of Glycine Amides via CDC Reaction Catalytic Nucleophilic Additions of Terminal Alkynes Li ous formaldehyde units, and a primary amine in a single synthetic operation by using a combined copper/rhodium catalyst (eq 20). 76 …”
Section: Addition Of Terminal Alkyne To Imine Tosylimine Iminium Iomentioning
confidence: 97%
“…Among notable recent efforts to develop new MCRs, 1 Bonfield et al recently reported an efficient method for the preparation of the isoindoline framework via a sixcomponent, tandem double A3-coupling and [2þ2þ2]-cycloaddition reaction. 2 Brauch et al have extended MCRs to seven components by taking advantage of the different chemoselectivities of the Ugi-Mumm and the Ugi-Smiles reaction. 3 Recently, the Orru group developed a one-pot reaction of up to eight components that involves nine new bond formations and eleven points of diversity.…”
Section: ' Introductionmentioning
confidence: 99%
“…Tetrasubstituted isoindolines can be synthesized readily from three alkyne units, two aqueous formaldehyde units and a primary amine in a single synthetic operation via a six-component coupling by using a combined copper/rhodium catalyst (eq. (27)) [128].…”
Section: Catalytic Nucleophilic Additions Via Ch Reactionmentioning
confidence: 98%